2012
DOI: 10.1530/joe-12-0341
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme 2, angiotensin-(1–7) and Mas: new players of the renin–angiotensin system

Abstract: Angiotensin (Ang)-(1-7) is now recognized as a biologically active component of the reninangiotensin system (RAS). Ang-(1-7) appears to play a central role in the RAS because it exerts a vast array of actions, many of them opposite to those attributed to the main effector peptide of the RAS, Ang II. The discovery of the Ang-converting enzyme (ACE) homolog ACE2 brought to light an important metabolic pathway responsible for Ang-(1-7) synthesis. This enzyme can form Ang-(1-7) from Ang II or less efficiently thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
377
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(391 citation statements)
references
References 199 publications
(207 reference statements)
7
377
1
6
Order By: Relevance
“…Other mechanisms that contribute to the therapeutic effects of ACE inhibitors and ARBs include increased bradykinin, angiotensin II, and angiotensin-(1-7) levels and increased activation of B 2 , AT 2 , and Mas receptors. [46][47][48][49] However, when given in combination with ACE inhibitors and ARBs, the renin inhibitor aliskiren may attenuate angiotensin II and angiotensin-(1-7) levels and thus Valsartan blocks the AT 1 receptor, PD123319 blocks the AT 2 receptor, and icatibant blocks the B 2 receptor. By blocking the tonic Ang II-mediated inhibition of renin secretion, valsartan increases renin, Ang I, and Ang II levels.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms that contribute to the therapeutic effects of ACE inhibitors and ARBs include increased bradykinin, angiotensin II, and angiotensin-(1-7) levels and increased activation of B 2 , AT 2 , and Mas receptors. [46][47][48][49] However, when given in combination with ACE inhibitors and ARBs, the renin inhibitor aliskiren may attenuate angiotensin II and angiotensin-(1-7) levels and thus Valsartan blocks the AT 1 receptor, PD123319 blocks the AT 2 receptor, and icatibant blocks the B 2 receptor. By blocking the tonic Ang II-mediated inhibition of renin secretion, valsartan increases renin, Ang I, and Ang II levels.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensinogen is converted into biologically inactive ANG-I by the enzyme renin, which in turn is converted into biologically active ANG-II by angiotensin-converting enzyme (ACE). Although recent studies have identified additional proteins interacting with ANG-II and renin, such as prorenin, renin receptors, and ACE-2, the enzymatic reactions resulting in the synthesis of ANG-II constitute the renin-angiotensin system (RAS; Santos et al 2013). Based on in vivo and in vitro studies, ANG-II is known to increase the expression and/or activities of all major transporters involved with Na C and acid transport in the various segments of the nephron, including Na C /H C exchanger 3 (NHE3; Geibel et al 1990, Cano et al 1994), H C -ATPase (Rothenberger et al 2007), epithelial Na C channel (Peti-Peterdi et al 2002), and thiazide-sensitive Na C -Cl K cotransporter (Sandberg et al 2007, San-Cristobal et al 2009, Castaneda-Bueno et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin-converting enzyme type 2 (ACE2), a pivotal RAS component, has been found in many regions in the bran, including SFO and PVN (8). Numerous studies have shown that ACE2 has opposite properties to that of the classic RAS via its conversion of angiotensin (ANG) II into ANG-(1-7) (20). We previously reported that overexpression of ACE2 in the brain blunts the development of hypertension in several animal models (9,31).…”
mentioning
confidence: 99%